Pembinaan Spiritual Masyarakat Air Kuning Desa Batu Merah Ambon melalui Khotbah Jumat Aktual - Syamsuar Hamka (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2023)
Broadly speaking, based on public opinion and the phenomena encountered, building an Islamic society requires the quality of material and presentation of actual khotbah. Moreover, in Batu Merah Village, Sirimau District, Ambon City, preachers are needed in filling out the Friday sermon schedule. Because of the scarcity of preachers, in the end many preachers tend to deliver khotbah with only scripts. The manuscript is then only read without paying attention to the context and conditions of the congregation. In the end, what happened was that the Friday sermon was only carried out as a ritual – a formality. Even though the momentum of Friday worship is very important to foster the spiritual quality of society. The Friday Sermon momentum is an opportunity to strengthen people's faith and beliefs, as well as directing them to adhere to Islamic teachings and Shari'a more firmly. Therefore, an actual Friday Sermon is needed that is oriented to the needs of the congregation. Especially on motivation in studying religious teachings. This activity is carried out to contribute to the spiritual development of society. Activities carried out with the lecture method. Where the congregation of al-Burhan mosque, Batu Merah Village numbered more than 100 people. The results of this activity can be seen by the condition of the congregation who are solemn and calm listening to the sermon. As well as testimonies from congregations who give appreciation to be able to develop it in other mosques.